Sankofa: Transcending the roots of incivility in professional nursing education in South Africa - Vink, Hildeguard J.-A.; Sefotho, Maximus M. (Curationis (Pretoria), 2025)
Background Professional nursing started with Florence Nightingale, who opened a School of Nursing in the mid-1800s. Her traditions of cleanliness, caring, peacefulness, charitability, diligence, responsibility, humaneness and compassion are still relevant to modern-day nursing. Uncivilised behaviour of students and nurse educators in professional nursing education is still evident. Objectives The objective of the study was to critically examine the roots of incivility in professional nursing education and to apply the wisdom of Sankofa to propel a renewed South African professional nursing education. Method The study employed a qualitative research method embedded in the interpretive framework, with an exploratory descriptive design. The study was conducted at a university-based nursing school and a nursing college in the Western Cape province. 25 participants (10 nurse educators and 15 nursing students) were recruited through purposive sampling. Data collection was performed through semi-structured individual, face-to-face interviews. The participants consented and volunteered to participate in the study, and all discussions were confidential and private. Elo and Kyngäs data analysis was employed. Results Conflicts with nursing norms, bureaucracy in nursing and professional nursing education, as well as the poor prestige of nursing and institutions of higher learning emerged as roots of incivility in professional nursing education. Conclusion The principles of Sankofaism can be applied to professional nursing education. Students and other key stakeholders can position professional nursing education firmly in Sankofaism. Contribution The article proposes Sankofaism as a framework to civil professional nursing education.